Health issues of Afghan refugees in California. - Lipson, J G (1992)
Since the 1979 Soviet invasion of Afghanistan, more than 6 million Afghan refugees have become the world's largest refugee population. Although refugees in Pakistan and Iran are now beginning to repatriate, continuing political turmoil in Afghanistan and children's acculturation and educational opportunities will keep many Afghans in the United States permanently. Although there are no accurate statistics, local resettlement agencies and Afghan community leaders estimate that there are 10,000 to 35,000 Afghans in northern California. They suffer from a variety of problems common to refugees: language, economic and occupational problems, and substantial challenges in psychological, family, social, and cultural adjustment to the United States. Although many Afghans are doing well, many others have depression, psychosomatic symptoms, and posttraumatic stress disorder.